Antecedents of Female Representation on Corporate Boards: An Exploratory Analysis at Board Level from a Socialized Perspective - Dang, Rey; Houanti, L’Hocine; Teulon, Frédéric; Vo, Linh-Chi (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
The literature explaining the representation of women on corporate boards (WOCB) has mainly relied on a rational economic perspective. Our study differs by relying on a socialized perspec-tive that is based on Schneider’s (1987) attraction-selection-attrition (ASA) model, Pfeffer’s (1983) organizational demography framework, and Tajfel and Turner’s (1986) social identity theory. We used a sample of French companies listed in the SBF 120 index during 2006-2010 to explore the impact of following antecedents of WOCB: male directors’ demographic traits, hu-man capital, and social capital.